A Survey of Chronic Pain Due to Spinal Dural Arteriovenous Fistulae. Issue 1 (July 2015) - Sasamori, Toru; Hida, Kazutoshi; Osanai, Toshiya; Yano, Shunsuke; Seki, Toshitaka; Houkin, Kiyohiro
Abstract : BACKGROUND: Chronic pain due to spinal dural arteriovenous fistulae (SDAVF) during follow-up is a serious issue because it can affect patients' quality of life. The severity of posttreatment chronic leg pain in patients with SDAVF is unclear. OBJECTIVE: To investigate the prevalence, severity, and characteristics of chronic leg pain in patients with SDAVF and to examine the clinical factors associated with chronic pain. METHODS: We conducted a survey of their chronic posttreatment leg pain in 49 SDAVF patients. It consisted of a numeric rating scale and a neuropathic pain symptom inventory (NPSI). Of the 49 patients, 32 (65.3%) completed the questionnaire. There were 24 males and 8 females whose mean age was 69.1 years. The mean follow-up period was 86.3 months. RESULTS: Chronic leg pain was reported by 26 (81.3%) of 32 patients; 14 experienced pain before treatment and 12 had new-onset posttreatment pain. The pain was reported as moderate to severe by 21 (80.8%) of 26 patients; the mean numeric rating scale and NPSI scores were 6.0 ± 2.3 and 17.4 ± 10.3, respectively. The NPSI subscores were significantly higher for spontaneous pain and paresthesia/dysesthesia than for paroxysmal pain. We found no significant clinical factors related to chronic posttreatment pain; on magnetic resonance imaging scans we identified spinal cord atrophy in 8 patients with chronic pain. CONCLUSION: Most of our SDAVF patients reported moderate to severe chronic leg pain characterized by spontaneous pain and paresthesia/dysesthesia. Spinal cord atrophy on magnetic resonance imaging scans was a characteristic in patients with chronic pain. ABBREVIATIONS: ALS, Aminoff-Logue scale NPSI, neuropathic pain symptom inventory NRS, numeric rating scale SCI, spinal cord injury SDAVF, spinal dural arteriovenous fistulae